OPTIMALISASI WORKSHOP KESADARAN GREEN ENTREPRENEURIAL BEHAVIOR DI KALANGAN WIRAUSAHA WANITA KOTA BATU - Ana Sofia Aryati; Khalilah Daud Isaac Makhmut (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Green or environmentally friendly entrepreneurial behaviour is independent business behaviour whose practices pay attention to the balance between economic aspects, organizational aspects and community aspects. The degradation of the quality of life's welfare forces humans to pay full attention to social, environmental and economic aspects as an embodiment of the concept of sustainable development, namely efforts to fulfil the needs of life today so as not to ignore the ability of future generations to be able to meet their needs. The aim of this activity is to improve technical and managerial skills in environmentally friendly entrepreneurs, build self-confidence, and empower women who work in the green economy sector in Batu City. Through the use of workshop-based methods, participants were trained to enhance environmental awareness and to manage their businesses in a more environmentally friendly manner. The outcomes of the activity included a significant improvement in participants' understanding of the importance of applying sustainability principles in business operations. Furthermore, the program successfully empowered women entrepreneurs by instilling a green entrepreneurship mindset that can drive economic growth, create job opportunities, and deliver substantial benefits to both society and the environment. This was reflected in the participants' enthusiasm during discussion sessions and their active engagement through questions, which facilitated a deeper understanding of the topics presented. The conclusion from this activity is that environmentally friendly entrepreneurship has a strategic role in supporting sustainable practices through a balance between economic, social and environmental aspects.